(untitled) (Journal of Atomic and Molecular Sciences, 2018)
A simple connection is established between aromaticity and overall stability of five-ring linear polyaromatic hydrocarbon oxyradicals. A chemically intuitive model is developed that exhibits a linear trend between an inexpensive geometric measure of aromaticity and the energetic stability of a model graphene edge with oxygen at different positions. It is believed to be an important step in establishing reaction pathways of soot and graphene oxidation.